Impact on flight trajectory characteristics when avoiding the formation of persistent contrails for transatlantic flights. (December 2018) - Yin, Feijia; Grewe, Volker; Frömming, Christine; Yamashita, Hiroshi
Highlights: Changes in trajectories for contrails avoidance follow a seasonal cycle. To avoid contrails, flight is detoured northward in summer and southward otherwise. A higher flight altitude helps avoid contrails regardless of seasons. The tradeoff between time and contrail distance shows a large daily variation. A partial mitigation plan enables a reasonable tradeoff between time and contrails. Abstract: This paper studies the impacts on flight trajectories, such as lateral and vertical changes, when avoiding the formation of persistent contrails for transatlantic flights. A sophisticated Earth-System Model (EMAC) coupled with a flight routing submodel (AirTraf) and a contrail submodel (CONTRAIL) is used to optimize flight trajectories concerning the flight time and the flight distance through contrail forming regions (contrail distance). All the trajectories are calculated taking into account the effects of the actual and local meteorological parameters, e.g., wind, temperature, relative humidity, etc. A full-year simulation has been conducted based on a daily flight schedule of 103 transatlantic flights. The trade-off between the flight time and contrail distance shows a large daily variability, meaning for the same increase in flight time, the reduction in contrail distance varies from 20% to 80% depending on the daily meteorological situation. The results confirm that the overall changes in flight trajectories follow a seasonal cycle corresponding to the nature of the potential contrail coverage. In non-summer seasons, the southward and upward shifts of the trajectories are favorable to avoid the contrail formation. In summer, the northward and upward shifts are preferred. A partial mitigation strategy for up to 40% reduction in contrail distance can be achieved throughout all the seasons with a negligible increase in flight time (less than 2%), which represents a reasonable trade-off between flight time increase and contrail avoidance.